The Validity of Property Ownership by Indonesian Citizens in Mixed Marriages: A Review of the Constitutional Court Decision No. 69/PUU-XIII/2015 - Nurjayanti, Florencia Devi; Sudiro, Amad (Jurnal Daulat Hukum, 2025)
The issue of property ownership by Indonesian citizens (WNI) in mixed marriages with foreign nationals (WNA) has long created legal uncertainty, particularly regarding land and building ownership. The main legal obstacle lies in Article 21 paragraph (1) of the Basic Agrarian Law (UUPA), which restricts ownership rights over land exclusively to Indonesian citizens. Consequently, an Indonesian citizen married to a foreign national without a prenuptial agreement is deemed to have community property, thereby making land or building ownership contradictory to national agrarian regulations. This study aims to analyze the validity of property ownership by Indonesian citizens in mixed marriages based on Constitutional Court Decision No. 69/PUU-XIII/2015. The research employs a normative juridical method, using statutory, conceptual, and case study approaches—particularly focusing on the reinterpretation of Article 29 of Law No. 1 of 1974 concerning Marriage. Through its decision, the Constitutional Court ruled that a marital agreement may be made not only before or at the time of marriage but also during the course of marriage. This ruling provides a new legal avenue for Indonesian citizens to retain ownership rights over land and buildings by creating a post-nuptial agreement that separates assets from their foreign spouse. The findings indicate that although the decision grants stronger constitutional protection for Indonesian citizens, its implementation still faces administrative challenges and disharmony among implementing regulations. The novelty of this research lies in identifying the Constitutional Court’s ruling as a form of substantive legal reform that harmonizes marriage law and national agrarian law, while simultaneously reinforcing the constitutional principles of legal certainty and equality for all citizens.